Evaluación de bloques nutricionales que incluyen vainas maduras de leguminosas arbóreas - Ayala-Monter, Marco Antonio; Rosales-Martínez, Gerardo Noe; Martínez-Martínez , Ricardo; Sanchez-Santillan, Paulino (Ecosistemas y Recursos Agropecuarios, 2025)
Nutritional blocks (NB) are a strategy to supplement nutritional deficiencies in animals. This study aimed to determine in vitro ruminal fermentative characteristics and NB consumption preferences in sheep. Four criollo sheep (30 ± 3.0 kg BW) were used. Feeding consisted ad libitum of pangola grass and treatments. The treatments were: T1 = NB control (without pods); T2 = NB with 15% algarrobo pods; and T3 = NB with 15% parota pods. In vitro ruminal fermentation characteristics and consumption preferences were evaluated. The experimental design for in vitro ruminal characterization was a completely randomized design, and Tukey's test (P ≤ 0.05) was used to compare means. A descriptive analysis was performed for consumption preference. In the in vitro assay, T2 showed the highest (P ≤ 0.05) cumulative biogas production at 2 hours of incubation. T1 showed higher biogas production at 6, 8, 10, 12, 24, 36, 48, and 72 hours of incubation, as well as cumulative production, metabolizable energy, dry matter degradation, and neutral detergent fiber (P ≤ 0.05). In the in vivo trial, consumption of pangola grass was 16.4% higher (P ≤ 0.05) compared to the consumption of nutritional blocks. The consumption of blocks with parota pods increased by 53.4% (P ≤ 0.05) compared to those containing carob pods and the control block. It is concluded that the inclusion of parota pods can be an alternative for use in nutritional blocks due to the preference registered in sheep.
Keywords: algarrobo; digestibility; sheep; parota; nutrient blocks